Snowball Throwing: An English Learning Method to Teach Descriptive Writing - Maulana Yusuf Aditya; Arfiyan Ridwan (Universitas PGRI Madiun, 2020)
Writing is a powerful multipurpose tool that helps us discover and explore more fully what we are thinking so that we learn as well as express our feelings and thoughts. One of reason that students lazy to written something because the methods are used by their teacher. Most of them still used direct learning method (extracurricular learning), the students were bored and they are did not enjoy when teaching learning process. So, that is why, in this study the writers try to use snowball throwing method to help students in learning descriptive writing. The data collection methods which used in this study are observation checklist and questionnaire checklist. Observation used to find out the implementation snowball throwing on students writing in descriptive text. The questionnaire was used to know the students’ responses after being taught descriptive text by using snowball throwing method. This study reveals that the highest aspect score of observation checklist in first observation is less, but in the second meeting, the writers found that highest aspect score of observation was good. Based on data questionnaire checklist, the writers found that the highest students’ responses were good. Based on this result data resource above, the writers concluded that the students could master writing after they were taught using snowball throwing in writing descriptive text. Finally, the writers suggested that the students had to practice their writing skill in many times. Besides, teacher had to have an interesting method in teaching writing descriptive text.